Grafted tubularised incised plate urethroplasty: an excellent option in primary hypospadias with poor urethral plate - Pan, Pradyumna (International Surgery Journal, 2017)
Background: Hypospadias represents the most frequent penile anomaly. The most challenging part of hypospadias surgery is urethral reconstruction. We here-in assess the cosmetic and functional outcome with primary single stage dorsal inlay urethroplasty using preputial skin grafts in tubularised incised-plate. We extended this indication to be the standard technique for primary hypospadias repair with poor urethral plate, flat glans and minimal ventral curvature. Methods: Children with a narrow urethral plate, shallow glans and minimal ventral curvature formed the study group. Children having severe chordee needing transection of the urethral plate,having undergone circumcision and failed hypospadias repair was excluded. This prospective study included the surgical experience of 87 cases of primary hypospadias operated upon between 2010 and 2016. Results: A straight penis was achieved in 97.7% of the patients with a 3.4% incidence of urethrocutaneous fistula. Acceptable cosmetic results were achieved in 96.5% of cases. Slit like appearance of neo urethral meatus was achieved in 96.5%, position was on the tip in 81 patients and in 6 it was mid glans. Glans dehiscence was seen in 3 patients. Meatal stenosis in 1, stricture, diverticulum and penile torsion was not seen in this series. Single and straight urinary stream was seen in 91.95%, splaying of urine in 3 patients and a thin stream in 4 patients. Conclusions: Primary dorsal inlay inner preputial graft urethroplasty successfully fulfils all traditional hypospadias repair criteria. It offers a viable option in the management of primary hypospadias with a narrow urethral plate.